EPS (Expandable Polystyrene) cement-based composite material for light thermal insulation structure and preparation method thereof

By introducing silica fume, ultrafine fly ash and polyethylene fibers into EPS cement-based composites, the problem of reducing density and non-compliance with the standards caused by adding insulating materials in concrete is solved, and the lightweighting of the material, thermal insulation, compressive strength and ductility are improved.

CN119874288APending Publication Date: 2025-04-25CHONGQING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510057580.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The addition of insulating materials in existing concrete leads to a decrease in density, and the strength does not meet the strength standards for structural applications, limiting the practical application of concrete.

Method used

By introducing silicon fume and ultrafine fly ash into the EPS cement-based composite, the fine pores are filled to improve the density and compressive strength; at the same time, polyethylene fibers are incorporated to enhance ductility and prevent the separation of EPS particles during the stirring process.

Benefits of technology

It realizes the lightweight and thermal insulation effect of EPS cement matrix composite materials, while improving the compressive strength and ductility of the material, meeting the strength standards for structural use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874288A_ABST
    Figure CN119874288A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of concrete, and particularly relates to an EPS cement-based composite material for a light thermal insulation structure and a preparation method of the EPS cement-based composite material. The EPS cement-based composite material is prepared from an adhesive, aggregate, water, a high-efficiency water reducing agent and polyethylene fibers, the adhesive is composed of cement, silica fume and superfine fly ash; the use amount of the silica fume is 0.15-0.17 time of the mass of the cement, and the use amount of the superfine fly ash is 0.7-0.9 time of the mass of the cement; the aggregate is expanded polystyrene particles or a mixture of expanded polystyrene particles and silica sand; the use amount of the aggregate is 0.0099 to 0.4645 times of the mass of the cement; the dosage of the water is 0.19-0.21 time of the mass of the adhesive; the use amount of the polyethylene fiber is 2% of the total volume of the EPS cement-based composite material. The compressive strength of the prepared EPS cement-based composite material exceeds 25 Mpa, and the ductility is 6%-10%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete, and specifically relates to an EPS cement-based composite material for a lightweight thermal insulation structure and a preparation method thereof. Background Art

[0002] Currently, 60% of the energy consumed by buildings is used for heating and cooling systems to maintain indoor comfort. This can be reduced by developing innovative materials with effective thermal insulation properties.

[0003] In the prior art, high thermal insulation materials such as foam, expanded perlite, expanded clay and expanded vermiculite, hollow glass, hollow fly ash microspheres and rubber crumbs are added to concrete to reduce its thermal conductivity, thereby significantly improving the thermal stability of concrete. The artificial defects induced by these insulating materials can also act as lightweight particles, thereby reducing the density of the concrete matrix and reducing the dead load of the concrete structure.

[0004] However, due to the increase of insulation materials in concrete, the insulation materials themselves have lower density and larger porosity, which will lead to a decrease in the density of the concrete as a whole, resulting in a decrease in the strength of the concrete. In most cases, the strength is lower than the 20MPa limit specified in the ACI specification. Therefore, when insulation materials are added to concrete, the strength of the concrete does not meet the strength standards for structural applications, which greatly limits the practical application of concrete. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides an EPS cement-based composite material for a lightweight thermal insulation structure and a preparation method thereof.

[0006] Expanded polystyrene, also known as Expandable Polystyrene or EPS for short, is a stable ultra-low-density polymer foam with discrete pores in its matrix. In the early exploration of the present invention, EPS particles were used as lightweight aggregates for concrete, and EPS was fused with concrete, aiming to develop a lightweight and environmentally friendly concrete material. Due to the low density and good thermal insulation of EPS particles, a uniformly distributed honeycomb structure is formed in the EPS cement-based composite material, which effectively reduces the total density of the EPS cement-based composite material and improves the thermal insulation performance of the EPS cement-based composite material. However, due to the low density, non-porosity and hydrophobicity of EPS, the mixture is easily separated during mixing with concrete, resulting in a reduction in the strength of EPS concrete; in addition, the brittleness of concrete itself also makes the ductility of EPS concrete insufficient.

[0007] Based on this, the present invention explores the dosage of lightweight EPS particles in aggregates, and uses an equal volume of EPS particles to replace silica sand in aggregates, thereby achieving the overall lightweight and thermal insulation effect of EPS cement-based composite materials. Due to the increase of EPS particles in aggregates, the strength of EPS cement-based composite materials is also reduced to a certain extent. Therefore, the present invention introduces silica fume and ultrafine fly ash as cementitious materials for concrete, and uses silica fume and ultrafine fly ash to fill the fine pores in EPS cement-based composite materials, thereby improving the density and compressive strength of EPS cement-based composite materials; by adding polyethylene fibers, the good interface bonding force between polyethylene fibers and the matrix is ​​utilized to enhance the ductility of EPS cement-based composite materials; at the same time, under the joint action of polyethylene fibers, silica fume and ultrafine fly ash, the segregation of EPS particles during the mixing process is prevented, and the stress concentration caused by EPS particles is reduced, thereby preventing the brittle fracture of EPS cement-based composite materials and improving the strength of EPS cement-based composite materials.

[0008] The first object of the present invention is to provide an EPS cement-based composite material for a lightweight thermal insulation structure. The EPS cement-based composite material is prepared from a binder, aggregate, water, a high-efficiency water reducing agent and polyethylene fibers.

[0009] The adhesive is composed of cement, silica fume and ultrafine fly ash; with cement as the matrix, the amount of silica fume is 0.15 to 0.17 times the mass of cement, and the amount of ultrafine fly ash is 0.7 to 0.9 times the mass of cement.

[0010] The aggregate is expanded polystyrene particles or a mixture of expanded polystyrene particles and silica sand; the amount of the aggregate is 0.0099 to 0.4645 times the mass of cement.

[0011] The amount of water used is 0.19 to 0.21 times the mass of the adhesive.

[0012] The amount of the polyethylene fiber is 2% of the total volume of the EPS cement-based composite material.

[0013] It should be noted that the present invention uses a material composed of cement, ultrafine fly ash and silica fume as a binder for EPS cement-based composite materials; by controlling the amount of silica fume to be 0.15 to 0.17 times the mass of cement, the amount of ultrafine fly ash to be 0.7 to 0.9 times the mass of cement, and by controlling the amount of water to be 0.19 to 0.21 times the mass of the binder, a higher compressive strength is achieved. The present invention explores the dosage of lightweight EPS particles, uses an equal volume of EPS particles to replace traditional silica sand as aggregate, forms EPS cement-based composite materials, and achieves the overall lightweight and thermal insulation effect of EPS cement-based composite materials. Due to the increase in low-density EPS particles, the strength of EPS cement-based composite materials will be reduced; therefore, the present invention adds silica fume, ultrafine fly ash and polyethylene fibers. Silica fume and ultrafine powder are used to fill the fine pores in the EPS cement-based composite material, thereby improving the density and compressive strength of the EPS cement-based composite material; and ultrafine fly ash is used to improve the fluidity of the EPS cement-based composite material, reduce the water demand, and increase the density and impermeability of the EPS cement-based composite material. In addition, the addition of silica fume and ultrafine fly ash can improve the low interface bonding strength and poor dispersibility between EPS and the matrix, thereby solving the problem of strength reduction and segregation of the EPS cement-based composite material caused by the addition of EPS. Preferably, the particle size of the ultrafine fly ash is 0.15μm to 34.25μm.

[0014] At the same time, the amount of polyethylene fiber incorporated in the present invention is 2% of the total volume of the EPS cement-based composite material. Due to the good interfacial bonding between the polyethylene fiber and the matrix, the polyethylene fiber can play a role in stress bridging and crack width control after the matrix cracks; when the cracks initiate, the fibers bridging the fracture surface promote load transfer through fiber bridging stress, thereby preventing the sudden expansion of the cracks; whenever the stress increases, cracks are generated in new areas instead of expanding existing cracks. This multiple crack mechanism greatly improves the ductility of EPS concrete. In addition, due to the high strength and high elastic modulus of the polyethylene fiber, a mesh distribution is formed in the concrete; and under the joint action of the polyethylene fiber, silica fume and ultrafine fly ash, the segregation of EPS particles during the mixing process is prevented, and the stress concentration caused by the inherent material defects, i.e., EPS particles, is reduced, thereby preventing the brittle fracture of EPS concrete and improving the strength of the EPS cement-based composite material. Preferably, the polyethylene fiber has a nominal tensile strength of 3000MPa, an elastic modulus of 120GPa, a density of 0.97g / cm, and a length of 12mm and a diameter of 26μm.

[0015] It should be noted that the present invention explores the dosage of lightweight EPS particles in aggregate, and the expanded polystyrene particles are used to replace silica sand in equal volume. When the aggregate is expanded polystyrene particles, the expanded polystyrene particles completely replace the same volume of traditional silica sand; when the aggregate is a mixture of expanded polystyrene particles and silica sand, the expanded polystyrene particles are 25% to 75% of the aggregate volume. Due to the low density and good thermal insulation of EPS particles, a uniformly distributed honeycomb structure is formed in the EPS cement-based composite material, which effectively reduces the total density of the EPS cement-based composite material and improves the thermal insulation performance of the EPS cement-based composite material. Preferably, the size of the EPS particles is 2 mm to 4 mm.

[0016] Preferably, the cement is ordinary Portland cement with a strength grade of 42.5. Cement is the main cementitious material of the EPS cement-based composite material and provides basic bonding strength for the EPS cement-based composite material.

[0017] Preferably, the high-efficiency water reducer is a polycarboxylate water reducer, which is used to improve the fluidity of the EPS cement-based composite material, reduce the water consumption of the EPS cement-based composite material, and improve the strength and density of the EPS cement-based composite material. Preferably, the high-efficiency water reducer is used in an amount of 1.8% to 2.4% of the mass of cement.

[0018] A second object of the present invention is to provide a method for preparing the EPS cement-based composite material, comprising the following steps:

[0019] S1. According to the ratio of raw materials for preparing the EPS cement-based composite material, a binder and an aggregate are mixed to obtain a mixture.

[0020] S2. Add water, high-efficiency water reducing agent and polyethylene fiber to the mixture in sequence and mix them to obtain slurry.

[0021] S3, pouring the slurry into a mold and curing it to obtain an EPS cement-based composite material.

[0022] Preferably, the curing temperature is 22°C to 28°C and the curing time is 24h to 36h.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The EPS cement-based composite material of the present invention uses cement as the main cementitious material, and forms hydrated calcium silicate with bonding force in the hydration reaction, which is the main source of the strength of the EPS cement-based composite material. By exploring the dosage of lightweight EPS particles, using an equal volume of EPS particles to replace traditional silica sand as aggregate, due to the low density and low thermal conductivity of EPS particles, a uniformly distributed honeycomb structure is formed in the EPS cement-based composite material, while achieving the overall lightweight and thermal insulation effect of the EPS cement-based composite material, the strength of the EPS cement-based composite material is reduced. The present invention utilizes the fine particle effect of silica fume and ultrafine fly ash to fill the fine pores between cement particles and increase the density of the EPS cement-based composite material; at the same time, silica fume and ultrafine fly ash can improve the low interface bonding strength and poor dispersibility between EPS and the matrix, thereby solving the problem of strength reduction and segregation of the EPS cement-based composite material due to the addition of EPS. In addition, under the joint action of polyethylene fiber, silica fume and ultrafine fly ash, the segregation of EPS particles during the mixing process is prevented, and the stress concentration caused by the inherent material defects, namely, EPS particles, is reduced, thereby preventing the brittle fracture of the EPS cement-based composite material and improving the strength of the EPS cement-based composite material. The overall strength of the EPS cement-based composite material prepared by the present invention is greater than 25Mpa.

[0025] In the EPS cement-based composite material of the present invention, polyethylene fibers form a network distribution in the EPS cement-based composite material due to their high strength and high elastic modulus, which can relieve the stress concentration caused by EPS when microcracks occur, thereby improving the fracture resistance. In addition, the high interfacial bonding stress between the polyethylene fiber matrix also plays a stress bridging role and a crack width control role. When cracks initiate, the fibers bridging the fracture surface promote load transfer through fiber bridging, thereby preventing the sudden expansion of cracks. Whenever stress increases, cracks will be generated in new areas instead of expanding existing cracks. This multiple crack mechanism greatly improves the ductility of concrete, and the ductility of the EPS cement-based composite material prepared by the present invention is 6% to 10%.

[0026] The EPS cement-based composite material of the present invention, through the synergistic effect of various preparation raw materials in the EPS cement-based composite material, makes the EPS cement-based composite material provided by the present invention not only have significantly improved strength and ductility, but also maintain low density and excellent thermal insulation performance, thereby solving the problems of low strength and poor ductility of existing lightweight EPS concrete. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1These are the particle size distribution diagrams and morphology diagrams of cement, silica fume, ultrafine fly ash, silica sand and EPS particles in the present invention, wherein Figure a is the particle size distribution diagram of cement, silica fume, ultrafine fly ash, silica sand and EPS particles, and Figure b is the actual morphology diagram of cement, silica fume, ultrafine fly ash, silica sand and EPS particles.

[0028] Figure 2 This is a relationship diagram between density and compressive strength of EPS concrete prepared in Examples 1 to 4 of the present invention and Comparative Example 1.

[0029] Figure 3 The tensile stress-strain curves of EPS concrete prepared in Examples 1 to 4 of the present invention and Comparative Example 1, wherein Figure a is the tensile stress-strain curve of EPS0, Figure b is the tensile stress-strain curve of EPS25, Figure c is the tensile stress-strain curve of EPS50, Figure d is the tensile stress-strain curve of EPS75, and Figure e is the tensile stress-strain curve of EPS100.

[0030] Figure 4 The figures are diagrams of the crack patterns after stretching of EPS concrete prepared in Examples 1 to 4 of the present invention and Comparative Example 1, wherein Figure (a) is a diagram of the crack patterns after stretching of EPS0, Figure (b) is a diagram of the crack patterns after stretching of EPS25, Figure (c) is a diagram of the crack patterns after stretching of EPS50, Figure (d) is a diagram of the crack patterns after stretching of EPS75, and Figure e is a diagram of the crack patterns after stretching of EPS100.

[0031] Figure 5 Thermal conductivity and thermal conductivity coefficient of EPS concrete prepared in Examples 1 to 4 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0032] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings.

[0033] In the description of the present invention, unless otherwise specified, all reagents used are commercially available and all methods used are conventional techniques in the art.

[0034] It should be noted that the English names and abbreviations of the raw materials in the EPS cement-based composite material of the present invention are: cement, whose full English name is cement, abbreviated as C; silica fume, whose full English name is silica fume, abbreviated as SF; ultrafine fly ash, whose full English name is ulrea-fine fly ash, abbreviated as UFFA; silica sand, whose full English name is silica sand, abbreviated as SS; expanded polystyrene, whose full English name is expanded polystyrene, abbreviated as EPS; water, whose English name is water, abbreviated as W; high-efficiency water reducing agent, whose English name is polycarboxylate superplasticizer, abbreviated as SP; polyethylene fiber, whose English name is polyethylene fiber, abbreviated as PE.

[0035] Example 1

[0036] This embodiment provides a method for preparing an EPS cement-based composite material.

[0037] The raw materials for preparing the EPS cement-based composite material of this embodiment are composed of a binder, aggregate, water, a high-efficiency water reducing agent and polyethylene fiber. In this embodiment, cement, silica fume and ultrafine fly ash are used as binders, and EPS particles and silica sand are used as aggregates. The amount of the aggregate is 0.4645 times the mass of cement; the expanded polystyrene particles are 25% of the volume of the aggregate.

[0038] The EPS cement-based composite material of this embodiment is prepared by the following steps:

[0039] S1. Using cement as a matrix, cement, silica fume, ultrafine fly ash, silica sand and EPS particles were mixed in a mixer for 2 minutes according to a mass ratio of cement, silica fume, ultrafine fly ash, silica sand and EPS particles of 100:16:80:44:2.45 to obtain a mixture.

[0040] S2. Add water and high-efficiency water reducer to the mixture in sequence, wherein the amount of water is 0.2 times the mass of the adhesive, and the amount of high-efficiency water reducer is 2.2% of the mass of cement. Stir for 8 minutes to obtain a mixed slurry, and then slowly introduce polyethylene fiber into the mixed slurry to ensure uniform dispersion, wherein the amount of polyethylene fiber is 2% of the total volume of the EPS cement-based composite material. Stir for 5 minutes to obtain a slurry.

[0041] S3. Pour the slurry into a mold, demould it after curing for 24 hours, and obtain a solid embryo; cure the solid embryo at a temperature of 25±3°C and a humidity of 50% to 60% for 28 days to obtain an EPS cement-based composite material, recorded as EPS25.

[0042] Example 2

[0043] This embodiment provides a method for preparing an EPS cement-based composite material.

[0044] The raw materials for preparing the EPS cement-based composite material of this embodiment are composed of a binder, aggregate, water, a high-efficiency water reducing agent and polyethylene fiber. In this embodiment, cement, silica fume and ultrafine fly ash are used as binders, and EPS particles and silica sand are used as aggregates, and the amount of the aggregate is 0.3048 times the mass of cement.

[0045] The EPS cement-based composite material of this embodiment is prepared by the following steps:

[0046] S1. Using cement as a matrix, cement, silica fume, ultrafine fly ash, silica sand and EPS particles were mixed in a mixer for 2 minutes according to a mass ratio of cement, silica fume, ultrafine fly ash, silica sand and EPS particles of 100:16:80:30:0.48 to obtain a mixture.

[0047] S2. Add water and high-efficiency water reducer to the mixture in sequence, wherein the amount of water is 0.2 times the mass of the adhesive, and the amount of high-efficiency water reducer is 2.1% of the mass of cement. Stir for 8 minutes to obtain a mixed slurry, and then slowly introduce polyethylene fiber into the mixed slurry to ensure uniform dispersion, wherein the amount of polyethylene fiber is 2% of the total volume of the EPS cement-based composite material. Stir for 5 minutes to obtain a slurry.

[0048] S3. Pour the slurry into a mold, demould it after curing for 24 hours, and obtain a solid embryo; cure the solid embryo at a temperature of 25±3°C and a humidity of 50% to 60% for 28 days to obtain EPS concrete, which is recorded as EPS50.

[0049] The difference between this embodiment and embodiment 1 is:

[0050] In this embodiment, the expanded polystyrene particles account for 50% of the aggregate volume.

[0051] Example 3

[0052] This embodiment provides a method for preparing an EPS cement-based composite material.

[0053] The raw materials for preparing the EPS cement-based composite material of this embodiment are composed of a binder, aggregate, water, a high-efficiency water reducing agent and polyethylene fiber. In this embodiment, cement, silica fume and ultrafine fly ash are used as binders, and EPS particles and silica sand are used as aggregates, and the amount of the aggregate is 0.1572 times the mass of cement.

[0054] The EPS cement-based composite material of this embodiment is prepared by the following steps:

[0055] S1. Using cement as a matrix, cement, silica fume, ultrafine fly ash, silica sand and EPS particles were mixed in a mixer for 2 minutes according to a mass ratio of cement, silica fume, ultrafine fly ash, silica sand and EPS particles of 100:16:80:15:0.72 to obtain a mixture.

[0056] S2. Add water and high-efficiency water reducing agent to the mixture in sequence, wherein the amount of water is 0.2 times the mass of the adhesive, and the amount of high-efficiency water reducing agent is 1.9% of the mass of cement. Stir for 8 minutes to obtain a mixed slurry, and then slowly introduce polyethylene fiber into the mixed slurry to ensure uniform dispersion, wherein the amount of polyethylene fiber is 2% of the total volume of the EPS cement-based composite material. Stir for 5 minutes to obtain a slurry.

[0057] S3. Pour the slurry into a mold, demould after curing for 24 hours, and obtain a solid embryo; cure the solid embryo at a temperature of 25±3°C and a humidity of 50% to 60% for 28 days to obtain an EPS cement-based composite material, recorded as EPS75.

[0058] The difference between this embodiment and embodiment 1 is:

[0059] In this embodiment, the expanded polystyrene particles account for 75% of the aggregate volume.

[0060] Example 4

[0061] This embodiment provides a method for preparing an EPS cement-based composite material.

[0062] The raw materials for preparing the EPS cement-based composite material of this embodiment are composed of a binder, aggregate, water, a high-efficiency water reducing agent and polyethylene fiber. In this embodiment, cement, silica fume and ultrafine fly ash are used as binders, and EPS particles are used as aggregates, and the amount of the aggregates is 0.0099 times the mass of cement.

[0063] The EPS cement-based composite material of this embodiment is prepared by the following steps:

[0064] S1. Using cement as the matrix, cement, silica fume, ultrafine fly ash and EPS particles were mixed in a mixer for 2 minutes according to the mass ratio of cement, silica fume, ultrafine fly ash and EPS particles of 100:16:80:0.99 to obtain a mixture.

[0065] S2. Add water and high-efficiency water reducer to the mixture in sequence, wherein the amount of water is 0.2 times the mass of the adhesive, and the amount of high-efficiency water reducer is 1.8% of the mass of cement. Stir for 8 minutes to obtain a mixed slurry, and then slowly introduce polyethylene fiber into the mixed slurry to ensure uniform dispersion, wherein the amount of polyethylene fiber is 2% of the total volume of the EPS cement-based composite material. Stir for 5 minutes to obtain a slurry.

[0066] S3. Pour the slurry into a mold, demould after curing for 24 hours to obtain a solid embryo, and cure the solid embryo at a temperature of 25±3°C and a humidity of 50% to 60% for 28 days to obtain an EPS cement-based composite material, which is recorded as EPS100.

[0067] The difference between this embodiment and embodiment 1 is:

[0068] In this embodiment, the expanded polystyrene particles account for 100% of the aggregate volume.

[0069] Example 5

[0070] This embodiment provides a method for preparing an EPS cement-based composite material.

[0071] The raw materials for preparing the EPS cement-based composite material of this embodiment are composed of a binder, aggregate, water, a high-efficiency water reducing agent and polyethylene fiber. In this embodiment, cement, silica fume and ultrafine fly ash are used as binders, and EPS particles and silica sand are used as aggregates. The amount of the aggregate is 0.4645 times the mass of cement; the expanded polystyrene particles are 25% of the volume of the aggregate.

[0072] The EPS cement-based composite material of this embodiment is prepared by the following steps:

[0073] S1. Using cement as a matrix, cement, silica fume, ultrafine fly ash, silica sand and EPS particles were mixed in a mixer for 2 minutes according to a mass ratio of cement, silica fume, ultrafine fly ash, silica sand and EPS particles of 100:15:70:44:2.45 to obtain a mixture.

[0074] S2. Add water and high-efficiency water reducer to the mixture in sequence, wherein the amount of water is 0.19 times the mass of the adhesive, and the amount of high-efficiency water reducer is 2.2% of the mass of cement. Stir for 8 minutes to obtain a mixed slurry, and then slowly introduce polyethylene fiber into the mixed slurry to ensure uniform dispersion, wherein the amount of polyethylene fiber is 2% of the total volume of the EPS cement-based composite material. Stir for 5 minutes to obtain a slurry.

[0075] S3. Pour the slurry into a mold, and demould after curing for 24 hours to obtain a solid embryo; cure the solid embryo at a temperature of 25±3° C. and a humidity of 50% to 60% for 28 days to obtain an EPS cement-based composite material.

[0076] Example 6

[0077] This embodiment provides a method for preparing an EPS cement-based composite material.

[0078] The raw materials for preparing the EPS cement-based composite material of this embodiment are composed of a binder, aggregate, water, a high-efficiency water reducing agent and polyethylene fiber. In this embodiment, cement, silica fume and ultrafine fly ash are used as binders, and EPS particles and silica sand are used as aggregates. The amount of the aggregate is 0.4645 times the mass of cement; the expanded polystyrene particles are 25% of the volume of the aggregate.

[0079] The EPS cement-based composite material of this embodiment is prepared by the following steps:

[0080] S1. Using cement as a matrix, cement, silica fume, ultrafine fly ash, silica sand and EPS particles were mixed in a mixer for 2 minutes according to a mass ratio of cement, silica fume, ultrafine fly ash, silica sand and EPS particles of 100:17:90:44:2.45 to obtain a mixture.

[0081] S2. Add water and high-efficiency water reducer to the mixture in sequence, wherein the amount of water is 0.21 times the mass of the adhesive, and the amount of high-efficiency water reducer is 2.2% of the mass of cement. Stir for 8 minutes to obtain a mixed slurry, and then slowly introduce polyethylene fiber into the mixed slurry to ensure uniform dispersion, wherein the amount of polyethylene fiber is 2% of the total volume of the EPS cement-based composite material. Stir for 5 minutes to obtain a slurry.

[0082] S3. Pour the slurry into a mold, and demould after curing for 24 hours to obtain a solid embryo; cure the solid embryo at a temperature of 25±3° C. and a humidity of 50% to 60% for 28 days to obtain an EPS cement-based composite material.

[0083] Comparative Example 1

[0084] This comparative example provides a method for preparing an EPS cement-based composite material.

[0085] The raw materials for preparing the EPS cement-based composite material of this comparative example are composed of a binder, aggregate, water, a high-efficiency water reducing agent and polyethylene fiber. Among them, this comparative example uses cement, silica fume and ultrafine fly ash as binders, and silica sand as aggregate, and the amount of the aggregate is 0.59 times the mass of cement.

[0086] The EPS cement-based composite material of this embodiment is prepared by the following steps:

[0087] S1. Using cement as a matrix, cement, silica fume, ultrafine fly ash and silica sand are mixed in a mixer for 2 minutes according to a mass ratio of cement, silica fume, ultrafine fly ash and silica sand of 100:16:80:59 to obtain a mixture.

[0088] S2. Add water and high-efficiency water reducer to the mixture in sequence, wherein the amount of water is 0.2 times the mass of the adhesive, and the amount of high-efficiency water reducer is 2.4% of the mass of cement. Stir for 8 minutes to obtain a mixed slurry, and then slowly introduce polyethylene fiber into the mixed slurry to ensure uniform dispersion, wherein the amount of polyethylene fiber is 2% of the total volume of the EPS cement-based composite material. Stir for 5 minutes to obtain a slurry.

[0089] S3, pouring the slurry into a mold, demoulding after curing for 24 hours, and obtaining a solid embryo; curing the solid embryo at a temperature of 25±3°C and a humidity of 50% to 60% for 28 days to obtain an EPS cement-based composite material, recorded as EPS0.

[0090] The difference between this comparative example and Example 1 is:

[0091] In this comparative example, silica sand was used as aggregate.

[0092] Examples 1 to 6 of the present invention all produce EPS cement-based composite materials that meet structural applications. The following examples 1 to 4 and comparative example 1 are used as examples for research, and the specific research methods and results are as follows:

[0093] Experimental testing

[0094] Figure 1 Figure 1 is the particle size distribution diagram and morphology diagram of cement, silica fume, ultrafine fly ash, silica sand and EPS particles, where Figure a is the particle size distribution diagram of cement, silica fume, ultrafine fly ash, silica sand and EPS particles, and Figure b is the actual morphology diagram of cement, silica fume, ultrafine fly ash, silica sand and EPS particles.

[0095] 1. Compressive strength and density test

[0096] According to the ASTM C109 compressive strength test standard, three cubic specimens of the EPS cement-based composite materials prepared in Examples 1 to 4 and Comparative Example 1 were subjected to compression tests. The size of each specimen was 50.8 mm × 50.8 mm × 50.8 mm. Before the test, the mass of each specimen was weighed and recorded, and its density was calculated using the density formula. The average density was determined based on the density results of the three specimens; the average compressive strength was determined based on the three compressive strength data. The results are shown in Table 1. Figure 2 shown.

[0097] Figure 2 The relationship between density and compressive strength of the EPS cement-based composite materials prepared in Examples 1 to 4 and Comparative Example 1 is shown in the figure, wherein the histogram is the compressive strength and the line graph is the density. Figure 2It can be seen from the histogram in that EPS particles are not added in Comparative Example 1, and the compressive strength of EPS0 reaches 83.9MPa. After adding EPS particles, the compressive strength values ​​of EPS25, EPS75, EPS50 and EPS100 are 45.5MPa, 43.7MPa, 39.9MPa and 27.8MPa, respectively. It is explained that with the increase of the content of lightweight EPS particles, the compressive strength of EPS cement-based composite materials is on a downward trend. In other words, the light weight and high compressibility of EPS particles reduce the density of EPS cement-based composite materials while also reducing the compressive strength of EPS concrete. However, due to the addition of silica fume, ultrafine fly ash and polyethylene fiber in the present invention, the compacting effect of silica fume and ultrafine fly ash is utilized, as well as the modification of silica fume, ultrafine fly ash and polyethylene fiber to EPS particles during stirring, and the segregation thereof is prevented and controlled, so that the overall strength of the EPS cement-based composite material prepared by the present invention is greater than 25MPa, which meets the structural use.

[0098] from Figure 2 As can be seen from the line graph in the figure, the density of EPS cement-based composites is significantly reduced after replacing silica sand with EPS. Specifically, the density is reduced from 2080 kg / m 3 Reduced to 1501kg / m in EPS100 3 . In addition, as the EPS content increases, the density of the EPS cement-based composite material gradually decreases, where the density of EPS25, EPS50, and EPS75 is 20%, 22%, and 25% lower than that of EPS0, respectively. This is very beneficial for reducing the deadweight of concrete structures. This reduction in deadweight subsequently leads to smaller component sizes and lower construction costs. Compared with the prior art, when the density is similar, the compressive strength of the EPS cement-based composite material containing EPS particles is about 2 to 5 times higher than that of ordinary EPS concrete.

[0099] 2. Tensile test

[0100] The uniaxial tensile test was carried out according to the JSCE uniaxial tensile test standard, with a gauge length of 80 mm, a width of 30 mm, and a thickness of 15 mm for each specimen. The test was carried out at a loading rate of 1 mm / min. The deformation within the gauge length was carefully tracked using two external linear variable displacement sensors fixed to the surface of the specimen. Each tensile parameter of the EPS cement-based composites prepared in Examples 1 to 4 and Comparative Example 1 was determined by the average of three uniaxial tensile test results.

[0101] The uniaxial tensile test results of the first crack strength, tensile strength and strain capacity of the developed cement-based composites containing different EPS contents within 28 days are shown in Table 1. The uniaxial tensile stress-strain curves are shown in Figure 3As shown in Table 1 and Figure 3 As shown in Figure 2, all EPS cementitious composites exhibited a robust strain hardening behavior characterized by a continuous increase in load capacity after the first matrix crack. The first cracking strength was defined as the stress level before the initial decrease in tensile stress, indicating the occurrence of the first matrix crack. The tensile strength was referred to as the maximum tensile stress observed in the curve, and the corresponding strain was determined as the strain capacity.

[0102] Table 1 Uniaxial tensile test results of EPS cement-based composite materials prepared in Examples 1 to 4 and Comparative Example 1

[0103]

[0104]

[0105] Table 1 shows the tensile test data of the EPS cement-based composites prepared in Examples 1 to 4 and Comparative Example 1. It can be seen from Table 1 that the addition of EPS particles significantly reduces the first crack strength of the EPS cement-based composite. The first crack strength is reduced from 4.9MPa in EPS0 to 1.7MPa in EPS100. This is because the interface transition zone between EPS and the cement matrix is ​​weaker than that between silica sand and the matrix. In addition, the presence of EPS particles is an artificial defect that exacerbates stress concentration. On the other hand, compared with EPS0, the tensile strength of EPS25, EPS50, EPS75 and EPS100 is reduced, of which the lowest tensile strength of EPS100 is 3.9MPa. This is because as the EPS content increases, the proportion of EPS in the weak area of ​​the cross section increases, resulting in a decrease in fiber content. It can be seen from the strain capacity data in Table 1 that the introduction of EPS significantly improves the strain capacity of EPS cement-based composites, especially in EPS100 and EPS75, the strain capacity reaches 10.0% and 9.6%, respectively. Compared with EPS0, the strain capacity is 2.85 times and 2.69 times that of EPS0. This shows that the introduction of EPS improves the ductility of EPS cement-based composites.

[0106] Table 2 Data on the number of cracks and crack width after stretching of the EPS cement-based composites prepared in Examples 1 to 4 and Comparative Example 1

[0107]

[0108] Table 2 shows the number of cracks and crack width data after stretching of the EPS cement-based composites prepared in Examples 1 to 4 and Comparative Example 1. As can be seen from Table 2, the introduction of EPS also reduces the crack width of the EPS cement-based composite, which plays an important role in improving the durability of the composite. In addition, the number of cracks in the cement-based composite with EPS added is between 59 and 120, while the number of cracks in EPS0 is 15, which is the reason why the EPS cement-based composite has high ductility.

[0109] Figure 4 The following are the crack pattern diagrams of the EPS cement-based composite materials prepared in Examples 1 to 4 and Comparative Example 1 after stretching, wherein Figure (a) is the crack pattern diagram of EPS0 after stretching, Figure (b) is the crack pattern diagram of EPS25 after stretching, Figure (c) is the crack pattern diagram of EPS50 after stretching, Figure (d) is the crack pattern diagram of EPS75 after stretching, and Figure e is the crack pattern diagram of EPS100 after stretching. Figure 4 It can be seen that with the increase of EPS particles, the crack width and the number of cracks after stretching gradually increase.

[0110] 3. Thermal conductivity test

[0111] Figure 5 is the thermal conductivity of the EPS cement-based composite material prepared in Examples 1 to 4 and Comparative Example 1. Figure 5 It can be seen that the addition of EPS reduces the thermal conductivity of EPS cement-based composites. With the increase of EPS content, from EPS0 to EPS100, the TC value decreases significantly from 1.59 W / m·K to 0.53 W / m·K, and the thermal conductivity decreases significantly by 67%.

[0112] This study aims to develop an insulating concrete suitable for independent structural applications that meets the dual requirements of structural strength and high ductility. To achieve this goal, two key performance parameters: compressive strength and strain capacity were comprehensively evaluated using the linear weighted average method. Given the equal importance of compressive strength and ductility to the overall material properties, both were given a weight of 0.5 in the calculation. The ratio of the weighted sum to the thermal conductivity was designated as the comprehensive performance index η.

[0113] like Figure 5As shown, EPS75 exhibits excellent overall performance in compressive strength, tensile ductility and thermal insulation. The compressive strength of EPS75 is 39.9MPa, the thermal conductivity is 0.64W / m·K, and the strain capacity is 9.6%. Compared with the compressive strength, thermal conductivity and strain capacity of the EPS0 cement-based composite material in Comparative Example 1, although the compressive strength and thermal conductivity of the EPS75 cement-based composite material are proportionally reduced, by 52% and 60% respectively, the strain capacity is significantly increased by 269%. This is due to the increase in EPS particles, which reduces the strength of the EPS cement-based composite material while achieving lightweight and thermal insulation performance. That is to say, the increase of EPS particles will reduce its compressive strength at the same time, and the present invention is to explore the optimal addition amount of EPS particles, and use the fine particles of silica fume and ultrafine fly ash to fill the fine pores between cement particles and increase the density of EPS cement-based composite materials; at the same time, silica fume and ultrafine fly ash can improve the low interface bonding strength and poor dispersibility between EPS and the matrix, thereby solving the problem of the strength decline of EPS cement-based composite materials due to the addition of EPS, and further improving the strength of EPS cement-based composite materials. The second is to use the high strength and high elastic modulus of polyethylene fibers to form a network distribution in EPS cement-based composite materials, and when microcracks occur, the stress concentration caused by EPS can be alleviated, thereby improving the fracture resistance. In addition, when cracks occur, due to the bridging effect of polyethylene fibers, cement-based composite materials can continue to bear loads, and multi-crack cracking behavior occurs, significantly improving its tensile strain capacity.

[0114] The EPS cement-based composite material prepared by the invention has an overall strength greater than 25Mpa and a ductility of 6% to 10%. The EPS cement-based composite material prepared by the invention has both high strength and high ductility, and meets the requirements of structural use.

[0115] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, once those skilled in the art know the basic creative concept, they can make other changes and modifications to these embodiments, and these changes and modifications all fall within the scope of the present invention.

[0116] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. If these modifications and variations of the present invention fall within the scope of the equivalent technology of the present invention, the present invention is also intended to include these modifications and variations.

Claims

1. An EPS cement-based composite material for lightweight thermal insulation structure, characterized in that: The EPS cement-based composite material is prepared from a binder, aggregate, water, a high-efficiency water reducing agent and polyethylene fibers; The adhesive is composed of cement, silica fume and ultrafine fly ash; with cement as the matrix, the amount of silica fume is 0.15 to 0.17 times the mass of cement, and the amount of ultrafine fly ash is 0.7 to 0.9 times the mass of cement; The aggregate is expanded polystyrene particles or a mixture of expanded polystyrene particles and silica sand; the amount of the aggregate is 0.0099 to 0.4645 times the mass of cement; The amount of water used is 0.19 to 0.21 times the mass of the adhesive; The amount of the polyethylene fiber is 2% of the total volume of the EPS cement-based composite material; The usage of the high-efficiency water reducing agent is 1.8% to 2.4% of the cement mass.

2. The EPS cement-based composite material according to claim 1, characterized in that: When the aggregate is a mixture of expanded polystyrene particles and silica sand, the expanded polystyrene particles account for 25% to 75% of the volume of the aggregate.

3. The EPS cement-based composite material according to claim 1, characterized in that: The EPS cement-based composite material has a ductility of 6% to 10% and a compressive strength of more than 25 MPa.

4. The EPS cement-based composite material according to claim 1, characterized in that: The size of the expanded polystyrene particles is 2 mm to 4 mm.

5. The EPS cement-based composite material according to claim 1, characterized in that: The polyethylene fiber has a length of 12 mm, a diameter of 26 μm, a nominal tensile strength of 3000 MPa, an elastic modulus of 120 GPa, and a density of 0.97 g / cm2.

6. The EPS cement-based composite material according to claim 1, characterized in that: The particle size of the ultrafine fly ash is 0.15 μm to 34.25 μm.

7. The EPS cement-based composite material according to claim 1, characterized in that: The cement is ordinary Portland cement with a strength grade of 42.

5.

8. The EPS cement-based composite material according to claim 1, characterized in that: The high-efficiency water reducer is a polycarboxylate water reducer.

9. A method for preparing the EPS cement-based composite material according to any one of claims 1 to 8, characterized in that: The following steps are involved: According to the ratio of the raw materials for preparing the cement-based composite material, weigh the adhesive and the aggregate; mixing a binder and an aggregate to obtain a mixture; Adding water, a high-efficiency water reducing agent and polyethylene fiber to the mixture in sequence and mixing them to obtain a slurry; The slurry is poured into a mold and cured to obtain an EPS cement-based composite material.

10. The method for preparing the EPS cement-based composite material according to claim 9, characterized in that: The curing temperature is 22° C. to 28° C., and the curing time is 24 h to 36 h.